Kajian Farmakoinformatika Senyawa Alkaloid Anggur Laut (Caulerpa racemose) Sebagai Inhibitor Collagenase Dalam Mekanisme Antiaging - Dewi Ratih Tirto Sari; M.Eko Pranoto; Siti Zamilatul Azkiyah (UNIVERSITAS PGRI MADIUN, 2022)
Caulerpa racemosa or sea grape is an edible macroalgae, cultivated and wild species in Asia ocean. Sea grapes also well known as functional food source from marine, contains high protein, fibers and secondari metabolites. The biological functionsÂ of sea grape also has been identified as antioxidant, antiinflammatory, antiobesity, and anticancer. However, the antiaging activity has not been known yet. This study investigated the potential antiaging activity of alkaloids compounds from sea grapes through inhibiting collagenase protein by farmacoinformatic study. six alkaloid structure of sea grapes including Caulerpin, Caulersin, Caulerchlorin, Racemosin A, Racemosin B, and Racemosin C, were retrieved from PubChem database and collagenase protein also was downloaded from Protein Data Bank with ID 2TCL. Six alkaloids of Caulerpa racemosa were redocked with collagenase at the specific site and were visualized by Discovery studio version 21.1.1. collagenase inhibitor compound also used as control for this study. farmacoinformatic analysis performed that six alkaloid of sea grapes and inhibitor compounds were showed at the same region of collagenase, which was identified as inhibitor sites. Several active residues of collagenase, involved SER139, PRO138, HIS128, and LEU81 were detected at six alkaloids compounds and control inhibitor, indicating six alkaloid of sea grapes potentially as collagenase inhibitor leading to antiaging properties. This study summarized that the six sea grapeâ€™s alkaloid has potential as collagenase inhibitor. Further in vivo analysis were required for further investigation.